The Role Of The Project Method In Forming Students' Self-Development Competence - Shabon FARMONOVA (Global Scientific Publishing, 2025)
This article discusses the importance of the project method in the formation of students' self-development competence and its role in the educational process. Self-development competence refers to the ability of students to independently improve their knowledge and skills, to strive for personal growth and development. The project method allows students to demonstrate their potential through practical activities, develop creative thinking and problem-solving skills. This article analyzes the role and impact of the project method in the formation of students' self-development competence, shows its effectiveness in the education system, as well as its positive impact on the personal and professional development of students. The article contains methodological recommendations aimed at developing students' skills in independent thinking, self-analysis and the application of new knowledge in practice
Keywords: creativity; communication; logic; thought